2020
DOI: 10.1016/j.ijpsycho.2020.09.019
|View full text |Cite
|
Sign up to set email alerts
|

A dimensional investigation of error-related negativity (ERN) and self-reported psychiatric symptoms

Abstract: Alterations in error processing are implicated in a range of DSM-defined psychiatric disorders. For instance, obsessive-compulsive disorder (OCD) and generalised anxiety disorder show enhanced electrophysiological responses to errors—i.e. error-related negativity (ERN)—while others like schizophrenia have an attenuated ERN. However, as diagnostic categories in psychiatry are heterogeneous and also highly intercorrelated, the precise mapping of ERN enhancements/impairments is unclear. To address this, we record… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 94 publications
(142 reference statements)
1
17
0
Order By: Relevance
“…During the in-person EEG session, participants completed the following two tasks: the modified Eriksen flanker task ( Eriksen and Eriksen, 1974 ) and the two-step reinforcement learning task ( Daw et al, 2005 , 2011 ). Data from the former task have been published previously ( Seow et al, 2020 ), but note that we also reported the basic association with compulsivity and model-based planning in that article, which served to contextualize a null result. Once participants had completed both tasks, they completed a short IQ evaluation before debriefing.…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…During the in-person EEG session, participants completed the following two tasks: the modified Eriksen flanker task ( Eriksen and Eriksen, 1974 ) and the two-step reinforcement learning task ( Daw et al, 2005 , 2011 ). Data from the former task have been published previously ( Seow et al, 2020 ), but note that we also reported the basic association with compulsivity and model-based planning in that article, which served to contextualize a null result. Once participants had completed both tasks, they completed a short IQ evaluation before debriefing.…”
Section: Methodssupporting
confidence: 74%
“…The effect size indicated that N = 150 participants were required to achieve 90% power at 0.05 significance. Our final sample was larger than this to achieve the required power for another study that the same subjects participated in ( Seow et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the ERN was not significantly cross-sectionally correlated with baseline depression symptoms. While several studies have demonstrated that depression is associated with a blunted ERN (Ladouceur et al, 2012;Ruchsow et al, 2004Ruchsow et al, , 2006Schoenberg, 2014;Schrijvers et al, 2009), other studies have demonstrated an enhanced ERN in depression (Aarts et al, 2013;Chiu & Deldin, 2007;Holmes & Pizzagalli, 2008, 2010Tang et al, 2013) and others have found no such associations between the two (Bress et al, 2015;Ruchsow et al, 2004;Seow et al, 2020;Weinberg et al, 2012). Some have suggested that these inconsistencies are due in part to the diagnostic heterogeneity of depression, such that symptoms of anhedonia and psychomotor retardation more strongly relate to a blunted ERN than other depression symptoms (Olvet et al, 2010;Schrijvers et al, 2008;Weinberg, Kotov, & Proudfit, 2015;Weinberg, Liu, & Shankman, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…An association with anxious apprehension was further supported by a study that compared groups with symptom profiles of OCD, worry, and anxiety symptoms and linked increased ERN amplitudes specifically to worry (Zambrano‐Vazquez & Allen, 2014). However, other studies failed to replicate the association between anxious apprehension and ERN (Härpfer et al, 2020; Muir et al, 2020) and it has been suggested that the anxiety‐ERN relationship might be stronger or even specific to clinical samples (Härpfer et al, 2022; Saunders & Inzlicht, 2020; Seow et al, 2020).…”
Section: Introductionmentioning
confidence: 99%